Effect of three insect-resistant maizes expressing Cry1Ie, Cry1Ab/Cry2Aj and Cry1Ab on the growth and development of armyworm Mythimna separata (Walker) - Hong-hua SU; Tao JIANG; Yu SUN; Hui-jie GU; Jiao-jiao WU; Yi-zhong YANG (Journal of Integrative Agriculture, 2020)
Three transgenic maize events (IE09S034, Shuangkang 12–5 and C0030.3.5) produced Cry1le, Cry1Ab/Cry2Aj and G10-EPSPS, Cry1Ab and EPSPS, respectively, all of which target the Asian corn borer. The oriental armyworm Mythimna separata (Walker) is the secondary target. In this study, the effects of the three Bt maizes on the development and survival of armyworm were studied. The results showed that IE09S034 had insecticidal activity against 1st instar larvae, and the survival rate of armyworm fed with Bt maize for 10 days was 46.2%, significantly lower than that of the control. The larvae at 3rd–6th instar were more tolerant of the Bt toxin than the early instar larvae. However, Shuangkang 12-5 had good insecticidal activity against 1st–5th instar larvae. The mortality was nearly 100% when the larvae were fed with Shuangkang 12-5 before 3rd instar, and the toxin had quick-acting efficacy. This event significantly inhibited the development of armyworm; that is, the larval duration of the 3rd and 4th instar larvae fed with Shuangkang 12-5 was prolonged by 4.5 and 3.0 days, respectively. The pupal weight and egg number were also significantly lower than those of the control. For C0030.3.5, it could control 1st–5th instar larvae effectively. The mortality rates were all over 50% if 1st–3rd larvae were fed with this event. The pupal weight of 4th–6th instar larvae fed with Bt maize were only 53.9, 56.8 and 54.6%, respectively, compared to that of the control. The number of eggs laid was significantly less than the control. The results indicate that all three transgenic maize events exhibit the potential to provide effective control of early instar larvae of armyworm, which can be commercialized in future to control lepidoptera pests such as Asian corn borer and armyworm.